Twig-like middle cerebral artery in a case of neurofibromatosis type 1 - Orciulo, Grazia Vittoria; Grasso, Daniela; Borreggine, Carmela; Castorani , Giulia; Vergara, Doriana; Nasuto, Michelangelo; Ciccarese, Giovanni; Popolizio, Teresa; Serricchio, Ettore; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2022)
Neurofibromatosis type 1 (NF1) is an autosomal dominant genetic disorder with multisystemic involvement, affecting central nervous system, skin, bone system and vessels, with a very heterogeneous clinical presentation. Vascular abnormalities are typically recognized in neurofibromatosis type 1 affecting cardiovascular and cerebrovascular systems. The incidence of circle of Willis anomalies in children with NF1 is twofold higher than in general population. In this paper, we report of 19-years-old female with NF1 and twig-like middle cerebral artery.